My ideal email day. Issue 8 (26th March 2019) - Kain, Daniel L.
Abstract : I made my usual swoop through email accounts early this morning, much like a city worker facing the toil of cleaning up after a rowdy parade that left only the remnants of what must have been fun for someone else. Surprisingly, I encountered an empty inbox for my work email. There was a moment of ecstasy, until I concluded there must be some sort of error in the system, because even though I'm currently enjoying a sabbatical leave, my inbox fills each day with requests, announcements, job postings, advertisements, and whatnot. It turns out that I was correct — the university email was down.